2021
DOI: 10.1007/s11739-021-02799-5
|View full text |Cite
|
Sign up to set email alerts
|

Does CHA2DS2-VASc score predict mortality in chronic kidney disease?

Abstract: Chronic kidney disease (CKD) is a leading cause of morbidity and mortality worldwide. Assessment of cardiovascular (CV) and all-cause mortality in CKD patients is of particular importance. CHA2DS2-VASc (congestive heart failure, hypertension, age ≥ 75 years, diabetes, prior stroke, vascular disease, age 65–74 years, and sex) score was originally formulated to predict the annual thromboembolic risk in patients with nonvalvular atrial fibrillation (AF). The calculation of R2CHADS2 and R2CHA2DS2VASc scores awarde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 40 publications
0
13
0
Order By: Relevance
“…Finding a good performance of the CHA 2 DS 2 -VASc score in predicting mortality also among patients with chronic kidney disease makes this score broadly usable. 2,19 Several reports have more recently shown the usefulness of the addition of the renal function to the CHA 2 DS 2 -VASc score as a predictor of CV events and mortality in different settings in patients with or without AF. 20,21 It is worth reminding that several studies have shown that renal insufficiency is in its own right a strong and independent predictor of all-cause mortality in different patient settings.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Finding a good performance of the CHA 2 DS 2 -VASc score in predicting mortality also among patients with chronic kidney disease makes this score broadly usable. 2,19 Several reports have more recently shown the usefulness of the addition of the renal function to the CHA 2 DS 2 -VASc score as a predictor of CV events and mortality in different settings in patients with or without AF. 20,21 It is worth reminding that several studies have shown that renal insufficiency is in its own right a strong and independent predictor of all-cause mortality in different patient settings.…”
Section: Discussionmentioning
confidence: 99%
“…Finding a good performance of the CHA 2 DS 2 ‐VASc score in predicting mortality also among patients with chronic kidney disease makes this score broadly usable 2,19 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Among the comorbidities more frequently associated with AF, chronic kidney disease (CKD) has special value, in consideration of the existing pathophysiological links, the influence of patient management, and treatments [ 4 ]. However, evidence gaps on the best strategies to adopt at specific stages of CKD are still present [ 1 , 4 , 5 , 6 ]. As a matter of fact, the stages of CKD, as proposed by Kidney Disease: Improving Global Outcomes (KDIGO) [ 4 , 7 , 8 ] are an important reference for clinical decisions and patients outcome in many cardiac diseases, both for medical and interventional treatments [ 9 , 10 , 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…Together with the HAS-BLED score, CHA 2 DS 2 -VASc is used to estimate the thrombotic/hemorrhagic risk in patients requiring thromboprophylaxis such as those with nonvalvular atrial fibrillation [11]. Nonetheless, the CHA 2 DS 2 -VASc score was reported to predict mortality in different groups of patients and conditions including subjects with chronic kidney disease [12], after cardiac [13] and noncardiac surgery [14], and acute cerebrovascular events [15]. Recent findings showed that the CHA 2 DS 2 -VASc score and its modified forms can differentiate patients at higher risk of worse outcome in course of SARS-CoV-2 infection [16][17][18].…”
mentioning
confidence: 99%